2019
DOI: 10.1111/hiv.12790
|View full text |Cite
|
Sign up to set email alerts
|

Lack of effectiveness of adherence counselling in reversing virological failure among patients on long‐term antiretroviral therapy in rural Uganda

Abstract: ObjectivesThe current World Health Organization and Uganda Ministry of Health HIV treatment guidelines recommend that asymptomatic patients who have a viral load (VL) ≥ 1000 HIV‐1 RNA copies/mL should receive adherence counselling and repeat VL testing before switching to second‐line therapy. We evaluated the effectiveness of this strategy in a large HIV treatment programme of The AIDS Support Organisation Jinja in Jinja, Uganda.MethodsWe measured the HIV VL at enrolment, and for participants with VL ≥ 1000 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 24 publications
2
21
1
Order By: Relevance
“…Most of those with failure had only 1 drug resistance mutation (largely NNRTI mutations) and 10 of the 12 participants with virologic had no TAMs, the mutations which are of most concern in terms of their effects on second-line therapy. These are in stark contrast to the patients who we found to have virologic failure during enrollment, [ 12 ] where we found that 83% had 2 or more mutations and 45% had ≥2 TAMs.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Most of those with failure had only 1 drug resistance mutation (largely NNRTI mutations) and 10 of the 12 participants with virologic had no TAMs, the mutations which are of most concern in terms of their effects on second-line therapy. These are in stark contrast to the patients who we found to have virologic failure during enrollment, [ 12 ] where we found that 83% had 2 or more mutations and 45% had ≥2 TAMs.…”
Section: Discussioncontrasting
confidence: 99%
“…We also enrolled participants with VL measurements of ≥1000 copies/mL but report on these elsewhere. [ 12 , 13 ] Study participants received an honorarium of 20,000 Ugandan shillings (approximately $5 US) to offset travel costs and a meal at each study visit. This study was approved by the Research Ethics Board of the University of British Columbia, the Uganda Virus Research Institute and the Uganda National Council for Science and Technology.…”
Section: Methodsmentioning
confidence: 99%
“…Patients' treatment buddies were also contacted when possible, although what transpired when they were contacted was not described. This approach was not found to be effective in this study, as 91% of participants remained unsuppressed with a VL > 1000 copies/mL after 3 months [61].…”
Section: General Adult Populationsmentioning
confidence: 69%
“…IAC is also known as enhanced adherence counselling (EAC) elsewhere in sub-Saharan Africa where it is standard of care for patients failing first- or second-line ART. A study in Uganda found that IAC was ineffective, with 91% of persons on first-line ART remaining virologically unsuppressed (VL > 1000 copies/ml) after 3 months [ 24 ]. In contrast, a study in South Africa found that enhanced adherence counselling was effective for patients unsuppressed on second-line ART [ 25 ].…”
Section: Discussionmentioning
confidence: 99%